An examination of the practice of chemistry through the lens of critical realism. Issue 4 (8th August 2022) - Blackie, Margaret A. L.
ABSTRACT: In this paper, the practice of chemistry is viewed in terms of the interaction of three elements – the physical world (at the molecular level), the conceptual world (the canon of chemistry) and the social world (the community of chemists). This interaction, which is based on critical realist ideas such as, for example, the transitive and intransitive dimensions of reality, affords a clear distinction between the practice of chemistry as science and the practice of chemistry as technology. It also shows the significance of the particularity of the chemist in the practice of chemistry. Finally, it allows a coherent philosophical foundation for chemistry research and chemistry education.